Effect of Soy Isoflavone on Prostate Cancer Cell Apoptosis Through Inhibition of STAT3, ERK, and AKT - Yoon-Jin Lee; Changyeol Lee; Dongsic Choi; Yeji Lee; Sang-Han Lee (Current Issues in Molecular Biology)
Genistein, an isoflavone found in soybeans, exhibits antioxidant, anti-inflammatory, and anticancer properties. This study explored the molecular mechanisms behind genistein’s anticancer effects in prostate cancer DU145 cells. In this study, genistein decreased cell viability, increased annexin V-PE(+) cells, and enhanced the sub-G0/G1 peak by flow cytometric analysis. Increased reactive oxygen species increased mitochondrial depolarization indicating mitochondrial dysfunction and inhibition of ATP formation were also observed in genistein-treated DU145 cells. Genistein upregulated p53 at the mRNA and protein levels and increased caspase-3/7 activity along with the cleavage of Bax, procaspase-3, and PARP. With the increasing genistein concentrations, the percentage of cells in the sub-G0/G1 peak and G2/M phase increased, which was inhibited by treatment with the pan-caspase inhibitor Z-VAD together with 100 μM genistein, which had little toxicity to normal prostate epithelial HPrEC cells. Genistein treatment simultaneously inhibited the activation of STAT3 and other closely related oncogenic kinases such as AKT and ERK and p38 and decreased VEGF expression. Taken together, these results suggest that genistein inhibits the growth of DU145 cells and induces apoptosis by inhibiting STAT3, AKT, ERK, and p38 which provides a molecular basis for the anticancer activity of genistein and suggests its potential as a valuable therapeutic candidate for prostate cancer.